2021
DOI: 10.1186/s13059-021-02302-5
|View full text |Cite
|
Sign up to set email alerts
|

ACME dissociation: a versatile cell fixation-dissociation method for single-cell transcriptomics

Abstract: Single-cell sequencing technologies are revolutionizing biology, but they are limited by the need to dissociate live samples. Here, we present ACME (ACetic-MEthanol), a dissociation approach for single-cell transcriptomics that simultaneously fixes cells. ACME-dissociated cells have high RNA integrity, can be cryopreserved multiple times, and are sortable and permeable. As a proof of principle, we provide single-cell transcriptomic data of different species, using both droplet-based and combinatorial barcoding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 82 publications
(72 reference statements)
4
101
0
Order By: Relevance
“…We carried out separate ACME dissociations for each developmental stage (Fig 1B) [3]. ACME allowed early fixation of cells and therefore reduced the stress responses that occur with enzymatic dissociations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We carried out separate ACME dissociations for each developmental stage (Fig 1B) [3]. ACME allowed early fixation of cells and therefore reduced the stress responses that occur with enzymatic dissociations.…”
Section: Resultsmentioning
confidence: 99%
“…Here we have also taken advantage of our recent advances in cell dissociation, combining ACetic-MEthanol (ACME) dissociation [3] and the SPLiT-seq scRNA-seq [59] technology to describe at cellular resolution spider embryogenesis at stages 7, 8 and 9. This has allowed us to define cell types and capture new candidate genes involved in several important developmental processes during these key stages of embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the analysis of single-cell gene expression variations in the special context of tissue is also a crucial perspective in the development of scRNA-seq technology, since the spatial variations of transcriptomic expressions in single cells throughout certain tissues are important evidence to unravel how cellular expressions change in response to the presence and proximity to other cells (Ståhl et al, 2016). The spacial analysis could be achieved by gene expression patterning technologies such as the application of in situ hybridization (ISH) or fluorescence in situ hybridization (FISH) to highlight marker genes and visualize cell morphology and gene expression locations (Horie et al, 2018;Soria et al, 2020;Chari et al, 2021;Garcıá-Castro et al, 2021). New techniques merging scRNA-seq and marker gene localization (e.g., spatial transcriptome techniques like SeqFISH+ and VISIUM) are urgently needed in the study of marine organisms (Ståhl et al, 2016;Longo et al, 2021).…”
Section: Future Directions Of Single-cell Sequencing On Marine Organismsmentioning
confidence: 99%
“…In addition, some studies have already shown the role that the epigenetic regulation and chromatin remodeling has on neoblasts maintenance and differentiation and will become another important field of study in the near future. Finally, the development of novel tools such as ACME maceration [151] that will allow for a better characterization of planarian cell types and lineages will definitely help to advance in our knowledge on how neoblasts drive regeneration in these amazing animals.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%